UBEM calibration method by energy consumption disaggregation using a change-point model - Kim, Hye Gi; Kim, Sun Sook (Journal of Building Performance Simulation, 2024)
Urban Building Energy Modeling (UBEM) is valuable for analyzing urban energy demand, but uncertainties can create gaps between predictions and actual usage. Calibration often uses utility bill data due to its urban-scale accessibility. However, comparing this data with simulation results for specific energy uses like cooling and heating is challenging. This study introduces a UBEM calibration method using a change-point model to disaggregate energy into heating, cooling, and base load. Applied to 222 office buildings in Seoul, this method provided more appropriate calibration results by considering individual energy consumption characteristics rather than just total consumption. The CVRMSE for base load, heating, and cooling energy decreased compared to uncalibrated simulations. This research highlights the importance of energy disaggregation when calibrating UBEM with utility bill data, offering a more nuanced approach to urban energy modeling.
Keywords: Building energy model; Calibration method; Change-point models; Disaggregation; Energy-consumption; Model calibration; Urban building energy modeling; Urban buildings; Urban energy; Utility bills; Calibration; Change point model; Urban building energy modelling; Utility bill